Development of Psychological Problems Among Adolescents During School Closures Because of the COVID-19 Lockdown Phase in Italy: A Cross-Sectional Survey - Esposito, Susanna; Giannitto, Nino; Squarcia, Antonella; Neglia, Cosimo; Argentiero, Alberto; Minichetti, Paola; Cotugno, Nicola; Principi, Nicola (Frontiers in Pediatrics, 2021)
Background: To evaluate adolescents’ psychological statuses and identify the risk and protective factors in the development of psychological problems among adolescents during school closures because of the COVID-19 lockdown phase in Italy, a cross-sectional survey was performed with an anonymous online questionnaire. Methods: A total of 2,064 adolescent students aged 11-19 years old (62.8% females; mean age, 15.4 ± 2.1 years), 69% of those initially included in the study, completed and returned the questionnaire. Results: Sadness was significantly more frequent in females (84%) than males (68.2%; p<0.001) and in the 14-19-year-old age group than the 11-13-year-old age group (79.2%; p<0.001). Missing the school community was a significantly more common cause of sadness in girls (26.5 vs 16.8; p<0.001), in southern Italy (26.45 vs 20.2; p<0.01) and in the 14-19-year-old group (24.2% vs 14.7%; p<0.001). The multivariate regression analysis showed that male gender was a protective factor against negative feelings (p <0.01), leading to a decrease of 0.63 points in the total negative feelings index. Having a family member or an acquaintance with COVID-19 increased the negative feelings index by 0.1 points (p <0.05). Conclusions: This study shows that school closures because of the COVID-19 pandemic outbreak caused substantial emotional uncertainty among adolescents, especially among females, and demonstrates that at schools there is an urgent need for prompt education on measures of COVID-19 prevention, such as the use of face masks, social distancing and handwashing, in order to avoid outbreaks.